SISTEM INFORMASI KEPEGAWAIAN PADA BALAI DILAT KEAGAAMAN MEDAN - Namira Syahputri Namira (Jurnal Ilmiah Sistem Informasi, 2023)
Employment information systems are government-developed systems that support systematic and accurate employment information systems. The problem mainly occurs in the employment section because the system is not fully utilized because it still USES the system manually, paging files in the cabinet and opening one file at a time to search for information on each employee is enough to consume time and energy. It's boring, so it's less efficient. The purpose of this study is to design an employment information system that is expected to support corporate performance in the field of resource information systems. The methodology used was stage one interview, the second stage of observation. The final phase of library research. On this final assignment we successfully made the software. Final results are also available for the agency. It is hoped that this software can help the employees' data processing system in the hall office be structured to repair and refine the information. The purpose of this research was to design an employment resource system that is expected to support corporate performance in the field of information system.